Peran Budaya Organisasi dalam Meningkatkan Kinerja Guru - Harmonika, Sri; Supiarmo, M. Gunawan (Jurnal Manajemen dan Budaya, 2025)
This study aims to determine the pattern of discipline coaching, the perceived importance of organizational culture in improving performance and motivating teachers, and inhibiting factors in improving teacher performance. This study uses a descriptive qualitative approach method. Data collection techniques through observation, interviews, and documentation studies. The subjects of the study included the principal, the teachers' council, and the school committee. Analysis of the research data shows: (1) Discipline coaching in improving teacher performance is oriented towards the rules that have been set, both laws and school regulations. The approach to teacher discipline coaching is carried out in stages or periodically, starting from determining job descriptions, taking a persuasive approach, supervising the learning process and guiding teacher tasks, and giving sanctions according to the level of violation. (2) The system for providing teacher motivation in improving their performance is carried out by providing non-binding incentives, good service, job promotions, opportunities to take part in training, providing work safety services, and teacher job comfort. (3) Inhibiting factors in improving teacher performance are the lack of socialization of school regulations, lack of coordination, ineffective communication between personnel, and lack of involvement of the school committee in making school decisions/policies.